Biopolymers in designing modern antimicrobial medical materials. Part 1, Biopolymer medical materials — collagen, chitosan - Gorczyca, G.; Tylingo, R. (Polimery, 2011)
The article is a review of the literature concerning the possible use of biopolymers for the preparation of dressings with antimicrobial activity. Authors show the potential of biopolymers: collagen and chitosan — which have the ability to immobilize and control the release of various active compounds — for providing the appropriate antibacterial, bacteriostatic and wound healing properties. Types of threats, for which the dressing materials should exhibit activity, were discussed. Specific kinds of biopolymers used for the production of medical materials and forms of their application were characterized. The second part of the paper is devoted to detail the main strategies used to impart antimicrobial activity to biopolymer materials.